FACTORS AFFECTING ON HIGH SCHOOL TEACHERS’ COMPTENCE AT PRIVATE HIGH SCHOOL IN YANGON, MYANAMR DURING PANDEMIC COVID-19 - Wai, Hnin Su; Santiparp, Prasak (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Teachers are the key implementers of the education system so their competence to teach during pandemic Covid-19 will contribute to continuing the quality education for the students. The aim of this research is to identify the factors affecting the high school teachers’ competence at private schools in Yangon, Myanmar during pandemic Covid-19. 261 private high school teachers from a total of 1,777 from the 4 districts of Yangon were selected using multi-stage random sampling. Sequential mixed-method was employed for the research. First phase was the qualitative study. 9 in-depth interviews were done at national level, school level and individual level stakeholders to find out the factors that may have impact on the private high school teachers’ competence during pandemic Covid-19. Second phase, the quantitative questionnaire was built based on the content analysis of the responses. Among the various factors learnt from the previous researches and qualitative interviews, stepwise multiple regression analysis revealed that the factors of (1) teachers’ motivation (2) preparation for the teachers (3) professional environment (4) teachers’ attitudes and (5) compensation are the predictive ones for the teachers’ competence. This paper explains the relation of the predictive factors as well as the relation between the motivation and the teachers’ competence employing the motivational theories.